Thermophysical Properties of Stainless Steel Containing 5 mass % B4C in the Solid Phase. (2nd September 2019) - Takai, Toshihide; Furukawa, Tomohiro; Yamano, Hidemasa
Abstract: This paper describes evaluation results of thermophysical properties of stainless steel (SS) containing 5 mass % boron carbide (B4 C) in its solid phase. First, the authors synthesized SS-B4 C samples with emphasis on 5 mass % B4 C and SS using a hot press method and then evaluated its homogeneity in several ways, such as chemical composition analysis, metallographic structure observation, and micro X-ray diffraction. This study also evaluated the density and the specific heat and thermal conductivity of the SS-B4 C sample and found that the density becomes lower and the temperature dependence of the density decreased as the temperature rose compared to that of stainless steel Type 316L (SS316L) used as a reactor material. The specific heat became slightly higher than that of SS316L and showed similar temperature dependence up to 1073 K. Unexpectedly, the thermal conductivity became lower than that of SS316L and showed similar temperature dependence up to 1273 K.